Performance of Slowly Driven Quantum Thermal Machines: Geometric Bounds and Many-Body Effects - Eglinton, Joshua (2024)
Thermal machines have played a historic role in enhancing our understanding of thermodynamics. Quantum thermal machines, which o↵er unique properties with no classical counterpart, such as coherence, entanglement and quantum collective effects, promise to replicate this success and provide insight into how the laws of thermodynamics extend to atomistic length and energy scales. Recently, success has been found in considering slowly driven microscopic engines, whose useful thermodynamic quantities such as power and efficiency, can be understood and related to each other in the form of trade-o↵ relations, in the so-called adiabatic response regime. Additional thermodynamic figures of merit such as constancy, which characterises the reliability of microscopic thermal machines against thermal and quantum fluctuations, play an important role at this energy scale and can also be included in this adiabatic response limit.